Exploring the COMPIN-10 and SUCOMP-10 Scales: Measuring Inferiority and Superiority Complexes Across Nine Countries - Đorđe Čekrlija; Julie Aitken Schermer; Ilija Dojčinovski; Nikola Miloš Rokvić; Yamen Hrekes; Bogdan Kalagurka; Lyudmyla Kolisnyk; Nurfitriany Fakhri; Shereena Naranath Mohammedali; Vojin Striković; Ivan Zečević (Psychological Topics)
This study introduces the short Inferiority Complex (COMPIN-10) and Superiority Complex (SUCOMP-10) scales. Participants (N = 4,010; 57% women), aged between 18 and 77 years (M = 29.68, SD = 10.62), were recruited from nine countries and completed the scales online in their native languages. The reliability, dimensionality, and convergent validity of the scales were examined. Satisfactory reliability coefficients were confirmed for both scales. The unidimensional structure of the COMPIN-10 scale was supported across country samples, whereas the SUCOMP10 scale did not exhibit a unidimensional structure. Additionally, the results indicated that the COMPIN-10 scale only achieved loading invariance, while the SUCOMP-10 scale lacked invariance across countries. The inferiority scores correlated negatively with self-esteem measures, extraversion, agreeableness, and conscientiousness, and the superiority scores correlated positively with self-esteem measures, extraversion, and conscientiousness, confirming the convergent validity of both scales in the respective country samples. The results of this multi-country study indicate that the COMPIN-10 scale is a more robust research instrument; however, further revision and refinement of both scales is recommended.